PENGARUH LAMA FERMENTASI TERHADAP CITA RASA NATA de Salacca - Junita Salelatu; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: Salak is one of Maluku's endemic fruits, especially in Buria Village which makes it the main outcome to increase people's income. Salak fruit contains quite complete nutritional elements such as energy, protein, carbohydrates, calcium, phosphate, iron, vitamin B, vitamin C, and water. To reduce the damage of fruit, the fruit of bark is processed into nata that has high nutritional and economic value. Making nata de Salacca assisted by microorganisms namely bacteria Acetobacter xylinum. In this case the microbes play an important role to overhaul substances that are difficult food absorbed by the body into food substances that are easily absorbed by the body. In addition, microbes provide flavor to the processed products. Methods: The duration of fermentation used in this study was 10 and 14 days. To determine the taste of nata de Salacca that has been processed then performed organoleptic test against 15 panelists. Result: The result is a brownish-white color, a slightly acidic sense of conformity, a chewy texture and a slightly acid-scented aroma, so there is a long-standing fermentation effect on the taste of nata de Salacca. Conclusion: The duration of fermentation has an effect on taste of nata de Salacca covering aspect of color, flavor, texture and aroma